Problems in Expressing Arabic Language of Indonesian Students at Khartoum International Institute for Arabic Language - Firdaus, Mochammad (Arabic Education Department, Islamic Studies Faculty, University Muhammadiyah of Malang, 2019)
This study was started with disclosure of issues faced by Indonesian students in Khartoum International Institute of Arabic Language. The main objective of this research revealed the ta?bir problem afflicting Indonesian students in learning classical Arabic, identifying the causes and knowing the impact of these problems in educational situations. To achieve the objective of this study, the method used by the researcher is descriptive analytical method. The results of this research are: 1) The ways which Indonesian students learned Arabic language in their institution have become instruments in improving Arabic language, 2) The impacts of the Indonesian dialects made difficulties for students in forming the Arabic dialect, 3) Environment in which treated the students outside the University affecting their ability in speaking classical Arabic, and 4) Weakness in disclosure affected students? academic achievement. Then the researcher suggested solutions to solve those problems such as: 1) To help the students to develop their process in traditional Arabic, it is needed to the students to take the benefits from any means, as teacher teaches them by reading newspaper, magazine and scientific journal which gave them increase the outcome of their linguistics ability, 2) The commitment from the lectures of all subjects to speak in well-structured Arabic and avoid using slank is needed.